Master Java web services and REST API with Spring Boot - Karanam, Ranga (Packt Publishing, 2018)
"Developing SOAP and RESTful web services is fun. The combination of Spring Boot, Spring Web MVC, Spring web services, and JPA makes it even more fun. Architectures are moving towards Microservices. RESTful web services are the first step to developing great Microservices. Spring Boot, in combination with Spring Web MVC (also called Spring REST) makes it easy to develop RESTful web services. There are two parts to this course: RESTful web services and SOAP web services. In the first part of the course, you will learn the basics of RESTful web services developing resources for a social media application. You will learn to implement these resources with multiple features such as versioning, exception handling, documentation (Swagger), basic authentication (Spring Security), filtering and HATEOAS. You will learn the best practices in designing RESTful web services. You will be using Spring (dependency management), Spring MVC (or Spring REST), Spring Boot, Spring Security (authentication and authorization), Spring Boot Actuator (monitoring), Swagger (Documentation), Maven (dependencies management), Eclipse (IDE), Postman (REST services client), and the Tomcat embedded web server. In the second part of the course, you will learn the basics of implementing SOAP web services by developing a few web services for a course management application. You will learn to use a contract first approach, defining XSD (XML Schema Definition) for your requests and responses. You will learn about WSDL (SOAP header, SOAP body and SOAP fault), XSD (XML schema definition) and JAXB (Java API for XML binding). You will implement three SOAP web services with exception handling and basic security (with WS security). In this part of the course, you will be using Spring (dependency management), Spring web services, Spring Boot, Spring Security (authentication and authorization), Swagger (documentation), Maven (dependencies management), Eclipse (IDE), Wizdler (SOAP services Chrome Plugin), and the Tomcat embedded web server. We will help you set up each one of these."--Resource description page